Individual Insurance Risk Propensity and Non-Mandatory Insurance Products Purchases: Evidence from Italy - Lippi, Andrea (International Journal of Economics and Financial Issues, 2025)
Based on a representative sample of Italian adults, this study aims to investigate the socio-demographic and socio-economic characteristics and the level of insurance knowledge influencing individual insurance risk propensity. Furthermore, it tests whether these factors influence the purchase of three non-mandatory insurance products, one comprising non-life insurance and for two life insurance. The obtained results demonstrate that there is no perfect relationship between determinants of individual insurance risk propensity and non-mandatory insurance product purchases. Specifically, the purchaser’s level of insurance knowledge does not influence insurance risk propensity but does influence the purchase of non-mandatory insurance products. This paper adds to the literature on the topic considering non-mandatory insurance products, studies being very rare, especially with reference to non-life insurance products. These results may assist policymakers and institutions in identifying areas of intervention and appropriate communication levers to direct attention toward the voluntary purchase of insurance products.